424 Large retrospective cohort of uterine sarcomas: poor survival of carcinosarcomas and leiomyosarcomas. (18th September 2019) - Plentz, TBS; Dias, LF; Santos, DZ; Silva, MLM; Torres, JCC; Vale, DB; Teixeira, J
Abstract : Objectives: To describe the diagnosis and outcomes of 122 cases of women with uterine sarcomas from a university hospital (Unicamp/Brazil). Methods: A retrospective cohort from 2001–2016 cases. Variables were described by proportions and analysed by Chi-Square or Fisher tests and survival by Kaplan-Meier survival curves and log-rank test. Results: Of the 122 sarcoma cases 77% were postmenopausal women, 46.7% were carcinosarcomas (CCS), 22% leiomyosarcomas (LMS), 16% endometrial stromal sarcomas (EES) and 13.9% adenosarcomas (ADS). A high proportion of stage I were find in EES (60%) and ADS (82%). Surgery was the first treatment in 78% with 79% performing adjuvant therapy and 22.1% were not able surgery, mainly in CCS (32%). Complete response was observed in 55 cases, and 20 relapsed (36%) at follow-up, 90% at three years. Overall survival was 76% at 12 months and 33% at 5 years, better for EES and ADS than for CCS and LMS (P=0.003). At the end of the study, 25% remained alive without disease and 57% had died from the disease, 78% of LMS and 61% of CCS (P=0.005). Conclusions: In this large cohort of uterine sarcomas, surgery was the first treatment in 78% of cases and overall 5-years survival was only 33%. Women with CCS and LMS showed a worse prognosis than women with EES and ADS.